2005
DOI: 10.1161/01.res.0000159181.06379.63
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Histone Modification and Cardiovascular Lineage Programming in Mouse Embryonic Stem Cells Exposed to Laminar Shear Stress

Abstract: Abstract-Experimental evidence indicates that shear stress (SS) exerts a morphogenetic function during cardiac development of mouse and zebrafish embryos. However, the molecular basis for this effect is still elusive. Our previous work described that in adult endothelial cells, SS regulates gene expression by inducing epigenetic modification of histones and activation of transcription complexes bearing acetyltransferase activity. In this study, we evaluated whether SS treatment could epigenetically modify hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
136
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(141 citation statements)
references
References 36 publications
4
136
1
Order By: Relevance
“…The points depicted in the figure represent both primary cells and cells lines, which have been demonstrated to have similar properties. 1 Pa = 10 dyn/cm 2 (after Anderson and Knothe Tate 2007a) [McBeath et al 2004, Meinel et al 2004, Knippenberg et al 2005, David et al 2007, Akimoto et al 2005, Baksh et al 2006, Campbell et al 2006, Takahashi et al 1998, Miyhanishi et al 2006, Hillsley and Frangos 1994, Billotte et al 2001, Klein-Nulend et al 1986, Wong and Carter 1990, Henderson et al 2007, Angele et al 2003, Roelofsen et al 1995, Illi et al 2005]. …”
Section: Discussion and Future Outlookmentioning
confidence: 99%
“…The points depicted in the figure represent both primary cells and cells lines, which have been demonstrated to have similar properties. 1 Pa = 10 dyn/cm 2 (after Anderson and Knothe Tate 2007a) [McBeath et al 2004, Meinel et al 2004, Knippenberg et al 2005, David et al 2007, Akimoto et al 2005, Baksh et al 2006, Campbell et al 2006, Takahashi et al 1998, Miyhanishi et al 2006, Hillsley and Frangos 1994, Billotte et al 2001, Klein-Nulend et al 1986, Wong and Carter 1990, Henderson et al 2007, Angele et al 2003, Roelofsen et al 1995, Illi et al 2005]. …”
Section: Discussion and Future Outlookmentioning
confidence: 99%
“…It has been shown that disrupting actomyosin tension generation by inhibiting myosin light chain kinase, RhoA, or Rho-kinase leads to global histone deacetylation, and conversely, increasing actomyosin contractility enhances histone acetylation levels in gastric carcinoma cells [41]. Increasing tension by application of shear stress leads to histone acetylation, chromatin remodeling, and changes in gene expression in endothelial and embryonic stem cells [54,55]. In agreement, experimental and theoretical evidence supports a specific role for the actin cytoskeleton in physically connecting sites of cell adhesion to ECM with the nucleus [51] as well as integrating changes in cell and nuclear shape [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Although consensus MAPK histone phosphorylation sites have not been described in vivo, MAPKs can activate histone-phosphorylating kinases (Cheung et al, 2000;Zhong et al, 2001). For example, ERK1/2 and p38a, -b can provoke changes in chromatin structure (Li et al, 2001;Illi et al, 2005;Schmeck et al, 2005) most likely owing to the activation of downstream kinases such as MSK1/2 (Saccani et al, 2002;Soloaga et al, 2003;Lee et al, 2006a;Vicent et al, 2006) or RSK2 (Cheung et al, 2000) that phosphorylate the N-terminal tail of histones. A surprising recent finding is that MAPKs bind to specific actively transcribed genes, as documented in yeast (Pokholok et al, 2006), reinforcing the idea that MAPKs participate actively in chromatin remodeling, perhaps explaining the observation that MAPKs such as p38a and ERK1/2 bind cellular DNA as judged by the use of chromatin immunoprecipitation assays in mammalian cells (Simone et al, 2004;Vicent et al, 2006).…”
Section: Signal Integration In the Nucleus: Spatiotemporal Regulationmentioning
confidence: 99%